Mammals of Colombia deposited at the Zoologische Staatssammlung Muenchen, Germany (2014)
The Zoologische Staatssammlung Muenchen (ZSM), Germany, possesses an historical value because is the depositary of important specimens that were used in the description of different species, especially from South America. Unfortunately, there is not available information about the mammals of Colombia housed at this collection. For this, 33 specimens from Colombia belonging to six orders, 14 genus, and 17 species were reviewed. Cranial and external measurements are given, as well as information of collectors and localities. Of these specimens, 23 were captured in Northern Colombia and imported to Germany to a pet store between 1954 and 1966. Due the difficulties to access to information of mammals from Colombia in European museums and collections, the information summarized here may be useful for people interested in these species.